2013
DOI: 10.1021/jf401612t
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Bioactivity of Monoterpenoids and Sesquiterpenoids from the Mycelia of Edible Mushroom Pleurotus cornucopiae

Abstract: Edible mushroom is a profilic source of bioactive metabolites for the development of drugs and nutraceuticals. In this work, four new monoterpenoids (1-4) and one new sesquiterpenoid (6) were isolated from the mycelia of edible mushroom Pleurotus cornucopiae fermented on rice. Their structures were established by nuclear magnetic resonance, mass spectrometry, and circular dichroism (CD) data analysis. Compound 1 possesses an unusual spiro[benzofuran-3,2'-oxiran] skeleton. The absolute configuration of the 6,7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 29 publications
1
39
0
1
Order By: Relevance
“…Compounds 1−5, 7, and 8 showed inhibitory activity against nitric oxide production in lipopolysaccaride-activated macrophages while compounds 6 and 7 exhibited cytotoxicity against HeLa and HepG2 cells. Wang et al (2013) P. eous Fatty acid esters, antibacterial activity Petroleum ether extract of the P. oeus fruiting bodies were analysed by CG-MS and 5 compounds were identified: cyclopentanetridecanoic acid, methyl ester; tartronic acid, (p-ethoxyphenyl), diethyl ester; 7, 10-octadecadenoic acid, methyl ester; heptadecanoic acid, 16-methyl, methyl ester and 9-octadecenoic acid [Z]-, 2-hydroxyl-1-[hydroxymethyl] ethyl ester. Among several crude extracts tested, only the petroleum ether extract showed strong antibacterial activity by inhibiting the growth of both gram positive and gram negative bacterial isolates.…”
Section: Pleutorus Sppmentioning
confidence: 99%
“…Compounds 1−5, 7, and 8 showed inhibitory activity against nitric oxide production in lipopolysaccaride-activated macrophages while compounds 6 and 7 exhibited cytotoxicity against HeLa and HepG2 cells. Wang et al (2013) P. eous Fatty acid esters, antibacterial activity Petroleum ether extract of the P. oeus fruiting bodies were analysed by CG-MS and 5 compounds were identified: cyclopentanetridecanoic acid, methyl ester; tartronic acid, (p-ethoxyphenyl), diethyl ester; 7, 10-octadecadenoic acid, methyl ester; heptadecanoic acid, 16-methyl, methyl ester and 9-octadecenoic acid [Z]-, 2-hydroxyl-1-[hydroxymethyl] ethyl ester. Among several crude extracts tested, only the petroleum ether extract showed strong antibacterial activity by inhibiting the growth of both gram positive and gram negative bacterial isolates.…”
Section: Pleutorus Sppmentioning
confidence: 99%
“…Homopolysaccharides, particularly glucans, are indeed the most responsible for mushrooms biological activities [26], and recent studies also revealed the therapeutic properties of mushrooms heteropolysaccharides [27]. Mushrooms are also rich in bioactive compounds [28][29][30], thus possessing radical scavenging activity and exerting antibacterial effects [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Mono-and sesquiterpenoids, ergosterol and fatty acid esters are low-molecular weight bioactive compounds identified in oyster mushrooms. Terpenoids exhibiting cytotoxicity towards HeLa and HepG2 cancer cells have been isolated from the P. cornucopiae mycelium (Wang et al, 2013). Menikpurage et al (2009) researched the antifungal activity of different fractions isolated from P. cystidiosus.…”
Section: Other Compoundsmentioning
confidence: 99%